2022
DOI: 10.1177/07334648221132792
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Coverage as a Social Determinant of Osteoporosis Diagnosis in a Population-Based Cohort Study of Older American Adults

Abstract: Social determinants of health theoretical frameworks identify health insurance coverage as a determinant of older adults’ osteoporosis diagnoses, which results in health inequities. In this research, we used the longitudinal Health and Retirement Study dataset of older United States adults, sampled biennially from 2012 to 2016. Logistic regressions estimated odds of osteoporosis diagnosis with and without a bone scan and/or hip fracture, holding insurance type, and health and demographic factors constant. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…For example, in 2 models, identifying as Black/African American is linked to lower odds of osteoporosis diagnosis. In Model 2 this is likely attributable to the exclusion of the bone density scan variable, which previous research has shown eliminates the racial/ethnic disparity in diagnosis 13 and was purposely added to show this phenomenon. However, this result also shows up in Model 6, which includes the bone density scan variable.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in 2 models, identifying as Black/African American is linked to lower odds of osteoporosis diagnosis. In Model 2 this is likely attributable to the exclusion of the bone density scan variable, which previous research has shown eliminates the racial/ethnic disparity in diagnosis 13 and was purposely added to show this phenomenon. However, this result also shows up in Model 6, which includes the bone density scan variable.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the theoretical background and depicted in the upper pathway of Figure 1 , allostatic load and other health-related factors may be influenced by exposure to structural and systemic inequalities. As osteoporosis diagnoses are tied to systemic/structural racism, and accessing a bone density scan tempers that effect, 13 we use a variable for whether the individual has had a bone density scan (binary; 0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations